Understanding the accountability and reporting practices on sustainability performance developed by the ethical mutual funds in the UK - Lopez, Angelica (2010)
The SR mutual funds have incorporated different approaches into the traditional investment criteria to tackle sustainability issues such as positive or negative screening, engagement, integration and best in class. These strategies seek to satisfy the variety of clients` values and interests and manage accordingly the investment`s risks. This offer of products not only generates financial profits, but also sustainability returns.